2018
DOI: 10.25159/2312-3540/3785
|View full text |Cite
|
Sign up to set email alerts
|

Factors Underlying Teacher Absenteeism in Selected Schools Located in Tshwane West District, South Africa

Abstract: Teacher absenteeism is widely recognised as a serious problem, particularly in disadvantaged areas, yet there is little systematic research and data on teacher absence in developing nations. Generally, literature discusses the phenomenon of teacher absenteeism on the basis of high-income countries and low-income countries. The current research argues that the reasons for teacher absenteeism in developed nations are largely personal matters related to the individual and the rate of absence is relatively low. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to Mashaba and Maile (2018), teachers in South Africa's disadvantaged communities, which include rural areas, are poorly compensated. Empirical literature concurs and points out that South African teachers in disadvantaged communities receive poor work resources compared to those in South Africa's highly developed communities (Naicker, 2000).…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mashaba and Maile (2018), teachers in South Africa's disadvantaged communities, which include rural areas, are poorly compensated. Empirical literature concurs and points out that South African teachers in disadvantaged communities receive poor work resources compared to those in South Africa's highly developed communities (Naicker, 2000).…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%
“…Studies that also looked at the causes of teacher absenteeism and job dissatisfaction in Africa's low-income countries concurred with the notion that the education system in disadvantaged communities is characterised by low incentives (pay, bonuses amongst others), poor working conditions and limited infrastructure (Abeles, 2009;Ejere, 2010;Yiga & Wandega, 2010). Mashaba and Maile (2018) further highlighted that poor compensation amongst rural teachers in South Africa stems from the country's macroeconomic policies. Although the growth, employment and redistribution (GEAR) macroeconomic policy framework has been side-lined after its adoption in 1996, Turok (2010) pointed out that its economic principles continue to dominate policy foundation in the country.…”
Section: Career Adaptability Work Resources and Employee Healthmentioning
confidence: 99%
“…The implication is that the absence of the teachers for less than 20 days is not treated as a serious breach of the employee-employer contractual obligation. Thus, this policy contributes to teacher absenteeism, which subsequently affects performance and productivity [24]. In Kenya, research on teacher absenteeism by Obiero, Mwebi, and Nyang'ara [25] found that the reasons for absenteeism are illness, personal or family problems, bereavement, and attending official duties.…”
Section: Causes Of Teacher Absenteeismmentioning
confidence: 99%
“…(Student teacher, undisclosed gender, date unknown) Unfortunately, ensuring quality placements in all WIL schools in South Africa is problematic (see Gravett & Jiyane 2019;Robinson 2015). According to , at least 75% of schools in the public system are described as dysfunctional, characterised by high levels of teacher absenteeism and late coming (Mashaba & Maile 2019) and as a result, most teachers do not cover the prescribed curriculum content and learners are not learning. This assertion is backed up by South Africa's poor performance in international benchmarking tests such as Progress in International Reading Literacy Study (PIRLS) over the periods (Howie et al 2017 and Southern Africa Consortium for Monitoring Educational Quality (SAQMEC) 2007 data (Taylor & Taylor 2013).…”
Section: Learning From Mentoring That Straddles Technical Mastery and Inquirymentioning
confidence: 99%